Brookite-TiO2‑Supported Pt Bilayers for the Low-Temperature Water–Gas Shift Reaction - Zhao, Wenning; Wang, Junjun; Zhang, Xixiong; Zhang, Guanghui; Li, Yong; Jiang, Zheng; Li, Mingrun; Zhou, Yan; Wang, Yuemin; Shen, Wenjie (ACS catalysis, 2024)
Highly dispersed Pt species, typically subnanometric clusters and single-atoms, feature catalysis that differed significantly from that of the faceted nanoparticles. However, the catalytic chemistry of these size-specified Pt entities is still a subject of debate. Here, we report that metallic Pt clusters in a bilayer geometry, dispersed on TiO2, served as the active phase for the low-temperature water–gas shift reaction. The control of Pt dispersion was done by treating a Pt/TiO2 sample, where 3 nm Pt particles dispersed over rod-shaped brookite-TiO2, with oxidative and reductive gases at elevated temperatures (673–873 K). The oxidative treatment of the Pt/TiO2 precursor yielded subnanometric PtO x clusters (<1 nm) at 773 K and cationic Pt single-atoms at 873 K. Combined microscopic and spectroscopic characterizations revealed that the PtO x clusters had a monolayer geometry, in which the Pt atoms were loosely connected via the Pt–O–Pt bond and chemically anchored on the surface of TiO2 via the Pt–O–Ti bond. While the cationic Pt single-atoms not only located on the surface but also diffused into the subsurface/bulk of TiO2, presenting in diverse coordination environments. Catalytic evaluations found that the subnanometric PtO x clusters were more active for the low-temperature water–gas shift reaction than the cationic Pt single-atoms. More interestingly, the H2-reduction of the PtO x clusters at 773 K resulted in metallic Pt clusters that adopted predominately a bilayer geometry at an appropriate Pt0/(Pt0 + Pt2+) ratio. The surficial metallic Pt atoms tuned the electronic structure of the positively charged Pt atoms at the Pt–TiO2 interface and thus enhanced the catalytic activity dramatically.